KAJIAN SOSIAL EKONOMI PENDIRIAN PUSAT PEMBELANJAAN MODERN RAMAYANA PLAZA DI PADALARANG, KABUPATEN BANDUNG BARAT (KBB) - Dindin Abdurohim (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Potential market (traditional and modern) can be an indicator or barometer of the dynamics of the economy. Commodity potential is certainly will stimulate their productivity if the place of marketing representative, consumers in other areas can easily access the products. The increasing productivity of people's economy will directly or not affect the increase in the revenue of the region, and public economy sector should be driven and developed optimally, considering it is big enough and great implication. This provides alternative and opportunities to the people of West Bandung Regence to have shopping places with complete facility, but it needs considering the aspect of social economy.